Electrocardiographic and Hemodynamic Effects of Intravenous Infusion of Bupivacaine, Ropivacaine, Levobupivacaine, and Lidocaine In Anesthetized Ewes. Issue 1 (1st January 2009) - Guinet, Patrick; Estebe, Jean-Pierre; Ratajczak-Enselme, Maja; Bansard, Jean-Yves; Chevanne, François; Bec, David; Lecorre, Pascal; Wodey, Eric; Ecoffey, Claude
Abstract : Background and Objectives: Neural blockade techniques are associated with a risk of acute cardiac toxicity after accidental intravenous (IV) injection of local anesthetics. The aim of this study was to compare electrocardiographic (ECG) and hemodynamic (HEM) effects induced by IV infusion of local anesthetics in an anesthetized ewe model. Methods: Thirty-two anesthetized ewes received IV bupivacaine (BUPI), ropivacaine (ROPI), or levobupivacaine (S-BUPI) at an equimolar dose, or lidocaine (LIDO) at a 3-fold higher rate (n = 8 in each group). RR, PR, QRS, and QT intervals (QTc ), changes (Δ) in systolic and diastolic arterial pressure (SAP and DAP), and in myocardial contractility (dP/dt), were assessed every 30 seconds for 7 minutes. From main ECG variables (RR, PR, QRS, QT), we proposed to use multiple correspondence analysis and hierarchical ascending classification to explore the structure of statistical dependencies among those measurements, and to determine the different patterns of ECG and HEM changes induced by infusion of BUPI, ROPI, S-BUPI, and LIDO. Results: Graphic representation of multiple correspondence analysis associated BUPI with the most pronounced modifications in ECG and HEM variables, followed by in decreasing order ROPI, S-BUPI, and LIDO. Comparisons of clusters identified by hierarchical ascending classification confirmed this classification for ECG variables. Ventricular tachycardia occurred only in the BUPI group. Conclusions: In our anesthetized ewe model, high dose IV infusion of BUPI induced the most marked changes in RR, PR, QRS, QT, QTc intervals, ΔSAP, and ΔdP/dt. ROPI altered ECG variables less than BUPI but more than S-BUPI. LIDO was associated with the smallest changes.